The Blood Donor Anxiety Scale: a six‐item state anxiety measure based on the Spielberger State‐Trait Anxiety Inventory. Issue 6 (28th March 2016) - Chell, Kathleen; Waller, Daniel; Masser, Barbara
Abstract : BACKGROUND: Research demonstrates that anxiety elevates the risk of blood donors experiencing adverse events, which in turn deters the performance of repeat blood donations. Identifying donors suffering from heightened state anxiety is important to assess the impact of evidence‐based interventions. This study analyzed the appropriateness of a shortened version of the state subscale of the State‐Trait Anxiety Inventory (STAI) in a blood donation context. STUDY DESIGN AND METHODS: STAI‐State questionnaire data were collected from two separate samples of Australian blood donors (n = 919 and n = 824 after cleaning). Responses to demographic, donation history, and adverse reaction questions were also obtained. Identification of items and analysis was performed systematically to assess and compare internal reliability and content, construct, convergent, and criterion validity of three potential short‐form state anxiety scales. RESULTS: Of the three short‐form scales tested, STAI‐State six‐item scale demonstrated the best metric properties with the least number of items across both sample groups. Cronbach's alpha was acceptable (α = 0.844 and α = 0.820), correlated positively with the original measure (r = 0.927 and r = 0.931) and criterion‐related variables, and maintained the two‐dimension factorial structure of the original measure. CONCLUSION: The six‐item short version of the STAI‐State subscale presented the most reliable and valid scale for use with blood donors. A validated donor anxiety tool provides a standardized assessment and record of donor anxiety to gauge the effectiveness of ongoing efforts to enhance the donation experience.